PEMBERIAN BAHAN ORGANIK DAN JENIS AIR PENYIRAM TERHADAP SIFAT FISIK TANAH ULTISOL DAN PRODUKSI TANAMAN ROSELLA (Hibiscus sabdariffa L.) - Gorretty Simanjuntak; Bintang Sitorus; Hardy Guchi (Universitas Sumatera Utara, 2013)
ABSTRACTThe objective of this research is to know the effect of the application of organic matter and kinds ofwater used on the physical characteristic of Ultisol and growth of Rosella plant(Hibiscus sabdariffa L). The research was conducted at compost centre, the screen house, and atChemistry and Fertility Laboratory, Research and Technology Laboratory, Faculty of Agriculture,USU Medan from May until November 2012. The design used was randomized block design(RBD) which consits of 2 (two) factors, Factor 1: Organic Matter (M) with 4 types: M0 = control,M1 = Ultisol 90% + shell 5% + compost of dust 5% , M2 = Ultisol 90% + shell 5% + compost ofstubbles 5% , M3 = Ultisol 90% + shell 5% + compost of corn 5%. Factor 2: Kinds of water used(A) with 3 (three) levels: A0 = water, A1 = the iron of water, A2 = urine, and 2 (two) replication tomeet 24 experimental units. The result of this research showed that organic matter decreased bulkdensity, increased of growth plant but did not effect the content of soil water level and productionof Rosella plant, kind of water increased soil water level but did not effect descrease bulk density,growth and production of Rosella plant and interaction of both treatmets increased growth of plantas 3 MST but did not affect physical characteristic of Ultisol and production of Rosella plant.Keywords: chemical property of ultisol, organic matter, kind of water used, and productionof rosella plant